Essential Minerals as a Factor in the Development of Acute Myocardial Infarction (Literary Review) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article provides a literary review of scientific articles using the resources of PubMed and Scopus search engines over the past 20 years, based on the following keywords in relation to the epidemiological situation of myocardial infarction, the features of the clinical course with a lack of trace elements.